A tough, anti-mildew and anti-counterfeiting soybean protein adhesive enhanced by gecko-inspired functional fiber and bio-based epoxide. (10th November 2021) - Zhou, Ying; Wu, Tiantian; Zeng, Guodong; Cai, Yahui; Luo, Jing; Li, Kuang; Tian, Dan; Li, Jianzhang; Fang, Zhen
Abstract: The development of efficient and sustainable formaldehyde-free adhesives has become an important strategy to solve the problems of environmental pollution, resource depletion and clean production. It is a promising and challenging task to prepare multifunctional adhesives with high adhesive strength from soybean protein (SP), an abundant and sustainable biomaterial that is largely produced from agricultural waste. Inspired by gecko toe, carboxylated paper fiber (CPF) anchored by MOFs (namely UiO66-NH2 @CPF) was constructed as micro-nano structure reinforcing phase, and resveratrol-based epoxide (RE) was employed as crosslinking agent to formulate a series of SP-based green adhesives. In particular, plywood bonded with SP/RE13/UiO66-NH2 @CPF1.5 presented the maximum dry/wet shear strength to 2.52 MPa and 1.43 MPa, which increased by 90.9% and 457% compared to that of adhesive made with SP alone, respectively. SP/RE13/UiO66-NH2 @CPF1.5 displayed a 92.02% residual rate (in water at 60 °C for 6 h), showing excellent bonding strength and water resistance. More importantly, SP/RE13/UiO66-NH2 @CPF1.5 successfully inhibited the invasion of mold, enabling to extend its shelf time to 12 h. In addition, it showed excellent fluorescent properties, exposing great potential in anti-counterfeiting of wood-based composite materials and information transmission. The development of SP-based adhesives improved the added value of industrial by-products, which not only met the demand for green and sustainable development, but also contributed to clean production by providing environmental and economic benefits along with excellent performance. Graphical abstract: Image 1